A molecular mechanism for transthyretin amyloidogenesis - Ai Woon Yee (Nature Portfolio, 2019)
A number of disease-causing human transthyretin (TTR) mutations are known to lead to amyloid formation. Here the authors combine neutron crystallography, native mass spectrometry and modelling studies to characterize the T119M and S52P-TTR mutants, providing mechanistic insights into TTR amyloidosis.